Wanprestasi Dalam Praktik Akad Istishna’ Terhadap Pengrajin Tenun Ditinjau Dari Kompilasi Hukum Ekonomi Syariah - Murni Cahnia; Mardona Siregar (Jurnal El-Thawalib, 2023)
This study examines default in the practice of istishna' contract against weaving craftsmen in terms of the Sharia Economic Law Compilation in Silangge Hamlet, Sipirok District, South Tapanuli Regency. This type of research is field research using a qualitative approach, the primary data source is data obtained directly through interviews with Silungkang weaving craftsmen in Silangge Hamlet, Sipirok District, South Tapanuli Regency and some of its consumers, secondary data sources are journal books and documents. related to this research, the data collection technique is by means of observation, interviews and documentation. Then the descriptive type of data analysis technique describes this research completely in a language so that an understanding in the field between reality and the language used does not reduce the existing data. The results of this study conclude that the causes of default in the practice of istishna' contract for weaving craftsmen are not on time to complete the ordered goods because the weaving machine is damaged or defective, too many orders, complicated motifs, and the difficulty of obtaining basic materials. Settlement of defaults carried out by craftsmen and consumers in a simple way, conducting deliberation between the two parties and making decisions so that no one is harmed. The review of the Compilation of Sharia Economic Law on defaults in the practice of itishna' contracts against weaving craftsmen is contained in Article 108 paragraph (2) If the object of the ordered goods does not match its specifications, the customer can use the right to vote (khiyar) to continue or cancel the order